2010
DOI: 10.1007/s00415-010-5754-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in young people with Tourette syndrome: a controlled study

Abstract: Quality of life (QoL) may be adversely affected by Tourette syndrome (TS). Although the core symptoms of this complex neurodevelopmental disorder are tics, patients often present with an array of behavioural difficulties, such as co-morbid obsessive compulsive disorder (OCD) or attention deficit hyperactivity disorder (ADHD). In this study we investigated whether young people with TS exhibited poorer QoL in comparison to healthy individuals and an epilepsy control group. We also analysed whether greater tic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 18 publications
(34 reference statements)
7
136
1
4
Order By: Relevance
“…Eddy et al also conducted the only controlled study specifically addressing HR-QOL in GTS to date, comparing the HR-QOL of young people with GTS with that of patients with epilepsy and healthy subjects [44]. In light of the controversy in previous research, these authors further examined whether tic severity or the presence of co-morbidities has a greater bearing on perceived HR-QOL.…”
Section: Studies Of Health Related-quality Of Life In Gilles De La Tomentioning
confidence: 99%
“…Eddy et al also conducted the only controlled study specifically addressing HR-QOL in GTS to date, comparing the HR-QOL of young people with GTS with that of patients with epilepsy and healthy subjects [44]. In light of the controversy in previous research, these authors further examined whether tic severity or the presence of co-morbidities has a greater bearing on perceived HR-QOL.…”
Section: Studies Of Health Related-quality Of Life In Gilles De La Tomentioning
confidence: 99%
“…Patients with TS have motor tics which are involuntary rapid and recurrent which can lead to severe ocular trauma [9][10][11]. Tics like head banging, punching and striking of the face or periorbital region can lead to direct coup injury to eye resulting in breakdown of formed vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these afflicted individuals are socially stigmatized [11,19]. Case studies have indicated that adult patients with GTS, compared with adults in the general population, show more dysfunction in their daily activities and a lower quality of life [20][21][22].…”
Section: ▪ Developmental Trajectory and The Apparent Decrease Of Ticsmentioning
confidence: 99%